The impact of comorbidity upon determinants of outcome in patients with lung cancer. Issue 2 (February 2015) - Grose, Derek; Morrison, David S.; Devereux, Graham; Jones, Richard; Sharma, Dave; Selby, Colin; Docherty, Kirsty; McIntosh, David; Nicolson, Marianne; McMillan, Donald C.; Milroy, Robert; ,
Highlights: Which combination of factors has the greatest impact on lung cancer survival? Survival appears to be determined by different factors which depend upon the stage of the cancer. This paper shows the importance of comorbidity particularly in early lung cancer survival. Abstract: Background: Survival from lung cancer remains poor in Scotland, UK. It is believed that comorbidity may play an important role in this. The goal of this study was to determine the value of a novel comorbidity scoring system (SCSS) and to compare it with the already established Charlson Comorbidity Index and the modified Glasgow Prognostic Score (mGPS). We also wished to explore the relationship between comorbidity, mGPS and Performance Status (PS). In addition we investigated a number of standard prognostic markers and demographics. This study aimed to determine which of these factors most accurately predicted survival. Methods: Between 2005 and 2008 all newly diagnosed lung cancer patients coming through the Multi-Disciplinary Teams (MDTs) in four Scottish Centres were included in the study. Patient demographics, World Health Organization/Eastern Cooperative Oncology Group performance status, clinico-pathological features, mGPS, comorbidity and proposed primary treatment modality were recorded. Univariate survival analysis was carried out using Kaplan–Meier method and the log rank test. Results: This large unselected population based cohort study of lung cancer patients has demonstrated that a number of important factors have significant impact in terms of survival. It has gone further by showing that the factors which influence survival are different, depending upon the stage of cancer at diagnosis and the potential treatment strategy. The novel comorbidity scoring system, the SCSS, has compared very favourably with the more established CCI. Conclusion: This study has identified that a variety of factors are independent prognostic determinants of outcome in lung cancer. There appear to be clear differences between the early and late stage groups.